Analysing Socio-Demographic Differences in Shopper’s Experiential Values: Illustration of Servicescape in Malaysia Department Store - Alias, Z.; Nawi, W.N.F.W.M.; Abbas, M.S.; Ghani, M.R.A. (International Journal of Engineering and Technology, 2018)
How servicescape influence on demographic differences in consumers’ experiential values are not extensively examined by researchers in context of department stores. The purpose of this study is to examine is there any significance on demographic differences in shoppers’ experiential values towards servicescape of department stores. 558 usable questionnaires were obtained across 5 regions in Malaysia and the analysis proceeded with both descriptive analysis and inferential analysis to test the model that was developed. The results indicate that shoppers’ age and income are really having a significant difference on how they experience the store environment. Meanwhile higher incomes group greater than RM9000 has a significant difference in their experience with group income of RM3001-RM5000. Group income greater than RM9000 has a different experience and perception on servicescape compared to other income groups. It indicates that the higher the incomes, the more reactive and concern to environmental contrast than those who have lower incomes. This finding will assist retailers to apprehend the effects of customers’ experiential values harmonised with the demographic characteristics affecting the servicescape offering. This could directly improve servicescape development strategies to produce unique in-store environment to boost shopping experiences and consequently leads to more satisfied shoppers especially in Malaysia.